Logo modernism - Müller, Jens 1982-; Wiedemann, Julius; Remington, R. Roger; Varea Riley, Isabel; Wulfekamp, Ursula; Fruhtrunk, Wolf (Taschen, 2018)
"Examine Modernism's distillation in graphic design with this vast collection of approximately 6,000 logos from 1940-1980. Ranging from media outfits to retail giant, airlines to art galleries, these clean, clear logo concepts may be seen as the visual birth of corporate identity"--Jacket.